The effects of COVID-19 on Central Florida’s community gardens: lessons for promoting food security and overall community wellbeing - Schanbacher, William D.; Cavendish, James C. (Frontiers in Public Health, 2023)
For quite some time, food systems scholars, public health workers, and food justice activists have recognized structural problems in the global food system that can cause food insecurity and inequitable access to nutritious foods. The COVID-19 pandemic and the accompanying disruption in food supply chains (FSCs) exposed these problems and raised questions about how community gardening and urban agriculture might offer some solutions. In this article, we examine the effects of the pandemic on the operations of community gardens in Central Florida and the attempts of these gardens to address the disruption in food supplies in their local communities. We do so by using data drawn from two research strategies employed by the members of University of South Florida’s Urban Food Sovereignty Group: (1) a survey conducted in 2021 of 45 leaders of community gardens throughout the Central Florida region; and (2) participation in the meetings and activities of a coalition of community gardens based in Tampa, Florida, from 2019 to 2022. Results reveal that although most community gardens in Central Florida were forced to change their routines in various ways (e.g., limiting the number of workers or volunteers who could work at the garden at the same time, or delivering workshops and education programs online instead of in-person), some gardens were able to maintain their regular operations and even reported increases in their membership or participation during the pandemic. Many community garden leaders also recognized the positive effect that community gardening seemed to have on their gardeners’ mental health, noting that their gardens became places of refuge for gardeners who sought safe, outdoor spaces, to relieve stress and interact with their neighbors. These same leaders also observed the effect of the pandemic on residents’ access to quality food, and intensified their efforts to provide more fresh food to pantries and traditional emergency food outlets. Survey respondents also shared important lessons they learned from the pandemic by suggesting that community gardens establish clear emergency protocols, use existing resources more efficiently, continue their educational programs, and strengthen their communications and cooperation with other gardens and actors in local food supply chains in order to ensure food security. We conclude by suggesting that one of the best ways that local communities can avert future food crises and strengthen their resilience is to root themselves more firmly in the principles of food sovereignty so they can sustain themselves when commercial FSCs are disrupted.